Loop to Acquisition of Cartographic Competence - Hüttermann, Armin; Fichtner, Uwe; Herzig, Reinhard (Journal of Geography Education, 2010)
Again and again, the public complains that school leavers are not sufficiently qualified to read maps, and this lack of "Graphicacy" is attributed to poor school teaching. This article analyses the map reading abilities of freshman students in geosciences and related curses. The empirical investigation verifies a statistically significant correlation between interest in maps, frequency of their utilization and aspects of cartographic competence. The statistical analysis of the extensive data collection reference to the existence of a positive loop: influence of interest in maps, their forms of representations and their possible applications to formation of cartographic competence. The investigation shows highly significant gender-specific differences.